EU ETS : first phase - Elias, Jaan; Scott Morton, Fiona; Mansur, Erin T.; Mitkowski, Allison; Zhao, Michelle (London : SAGE Publications Ltd, 2017)
In 2005, the European Union began a bold experiment in environmental regulation by instituting a cap and trade program for carbon emissions, the European Union Emissions Trading Scheme (EU ETS). Under the plan, the European Union's member states were allocated carbon allowances, which the states in turn distributed to industrial establishments within their jurisdictions. Those industrial concerns that emitted more carbon than their allocations covered would have to either curb their emissions or purchase carbon allowances from those establishments which had more carbon allowances than they needed. This, planners believed, would create an active market for carbon allowances.
Originally published in Elias, J., Scott Morton, F. M., Mansur, E. T., Mitkowski, A., & Zhao, M. (2009).EU ETS: First phase. 09-031. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol09.cases.som.yale.edu/eu-ets-first-phase.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Industrial management -- Environmental aspects -- European Union countries; Environmental policy -- European Union countries